Nailfold capillaroscopy—how many fingers should be examined to detect abnormality?. (21st September 2018) - Dinsdale, Graham; Roberts, Chris; Moore, Tonia; Manning, Joanne; Berks, Michael; Allen, John; Anderson, Marina E; Cutolo, Maurizio; Hesselstrand, Roger; Howell, Kevin; Pizzorni, Carmen; Smith, Vanessa; et al.
Abstract: Objectives: Nailfold capillaroscopy is being increasingly used by rheumatologists in the diagnosis of SSc. However, assessment of all nailfolds can be time-consuming in a busy outpatient clinic. Our aim was to answer the question as to how many (and which) fingers a clinician should routinely assess to capture accurately the true state. Methods: A total of 2994 assessments (by an international panel of expert observers) of 1600 images from 173 participants (101 with SSc, 22 with primary RP and 50 healthy controls) were included in this analysis. Seven single-finger or finger combinations (derived from the middle and ring fingers) were then tested for sensitivity for the presence of two markers of capillary abnormality [presence of giant capillaries and an SSc grade (early, active or late)] compared with assessment of all eight fingers. Results: For the eight-finger gold standard, sensitivity against the diagnostic criteria was 74.6% (53.0% for the presence of giants alone and 73.1% for image grade alone). Examining only one finger gave low sensitivity (ranging from right middle 31.7% to left ring 46.6%). Examining both ring fingers gave a sensitivity of 59.8%, whereas examining the four-finger combination of both ring and both middle fingers gave a sensitivity of 66.7%. Conclusion: During routine capillaroscopic examination, ideally all eight nailbeds (excluding thumbs) should be examined, otherwise some abnormalities will be missed. Examining only four fingers reduces capillaroscopy sensitivity.